Transient Gross Hematuria Following Urethral Catheterization in a Patient with Severe Intravesical Prostatic Protrusion: A Case Report from a Resource-Limited Setting - Muhammad Fadli; Welly Patanasalu (Jurnal Sehat Indonesia (JUSINDO), 2026)
Background: Gross hematuria in elderly men frequently raises suspicion of urological malignancy. However, benign anatomical conditions such as severe intravesical prostatic protrusion (IPP) may predispose patients to procedure-related bleeding, particularly following urethral catheterization. Objective: To describe transient gross hematuria following urethral catheterization in a patient with severe intravesical prostatic protrusion and to emphasize the importance of chronological clinical assessment in differentiating benign procedure-related bleeding from possible malignancy. Methods: This study is a descriptive single-patient case report. An 85-year-old man presented with acute urinary retention complicated by septic shock and acute kidney injury. Gross hematuria occurred immediately after urethral catheterization. Clinical evaluation included laboratory investigations and transabdominal ultrasonography. Results: Ultrasonography revealed severe benign prostatic enlargement (estimated volume 176 mL) with grade 3 IPP measuring 2.04 cm. The hematuria resolved spontaneously within 24 hours without clot formation or recurrence. No intravesical mass or hydronephrosis was identified. Conclusion: Severe IPP may predispose elderly patients to transient catheter-induced hematuria due to anatomical distortion and increased mucosal vulnerability. Recognition of this self-limiting presentation is particularly important in resource-limited settings to avoid unnecessary invasive investigations while maintaining appropriate oncologic vigilance.